In vitro antidiabetic effect of stigmasterol and chlorogenic acid - Mohmad, Mohamad Zulakmal (2017)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycaemia associated with disturbance in metabolism of carbohydrates, proteins and fats due to insulin insensitivity or inadequate insulin production from pancreas. Inhibition of carbohydrate hydrolyzing enzymes such as a-amylase and a-glucosidase can be the key for delaying the process of breaking down the carbohydrate, reduce post-prandial blood glucose absorption and reduce elevation of blood glucose level. Phytochemicals such as stigmasterol and chlorogenic acid are among the many that are obtained from plants, which may have antidiabetic property. This study was aimed to determine the inhibitory effect of stigmasterol and chlorogenic acid against a-amylase and a-glucosidase activity. Metformin was used as standard drug reference to replace acarbose. Stigmasterol has the strongest inhibitory effect against a-amylase with ICso value of 3.50 ± 2.39 µg/ml and chlorogenic acid was the most potent in inhibiting a-glucosidase with ICso value of 36.67 ± 14.43 µg/ml. However, Stigmasterol and chlorogenic acid have strong inbitory effect against a amylase and a-glucosidase activity more than metformin (IC50=326.67 ± 64.29 µg/ml and IC50=406.67 ± 5.78 µg/ml, respectively). In conclusion, this study suggest stigmasterol and chlorogenic acid can function as organic a-amylase and a-glucosidase inhibitors and have the possibility to effectively suppress postprandial hyperglycemia in patients with T2DM. However, potential indication of these two compounds need to be confirmed by conducting in vivo antidiabetic animal models and later on clinical trials for their effective utilization as therapeutic agents.